Role of Technology in Enhancing Teaching and Learning in Cambodian Higher Institutions: Implication for Stakeholders - Nelli Antepli; Yusuf Suleiman; Hameed Olalekan Bolaji; Semiu Olawale Makinde (Fakultas Keguruan dan Ilmu Pendidikan, 2019)
This paper examined the role of technology in enhancing teaching and learning in Cambodian higher institutions and its implication for stakeholders. Evaluation of ICT models, emerging technologies and the learning theories related to technology were systematically reviewed. An overview of teaching and learning before the digital age with a particular reference to history of education and technology in Cambodia was examined while historical theories of educational technology such as constructivism, complexity theory, the pedagogy of nearness, heutagogy, and connectivism were highlighted. Furthermore, emerging technology integration models such as SAMR, TPACK, UDL models were examined including the multiple roles of the learner, educator and the audience in a connected age.Several strategies in which technological tools that can be used to enhance students’ learning were provided. Part of the Implication of the study includes adequate provision of power supply, computer laboratories and internet connectivity in Cambodian higher institutions should be paramount to government, private firms, philanthropists and NGOs so that students can appreciate technology and learn fast. Aside that, adequate fund should be given to the institutions to procure other necessary technology gadgets that can be used to promote learning. Keywords: ICT Models, Teaching and Learning, Higher Institutions, Stakeholders, Cambodia